(untitled) (International Journal of Medical and Surgical Sciences, 2014)
The ultrasound is a noninvasive diagnostic method and gained increasing importance in the plane of the emergency. Their usefulness for the recognition of anatomical structures and detection of a difficult airway. This method increases the quality of care in the emergency room. The objective of the study was to evaluate the ultrasound’ training for the identification of normal and variation in the anatomic airway, and their usefulness during tracheal intubation. There were two periods of training. First period: 2013-February/2013 July, learning of normal human anatomy in cadaveric material corpses (in formaldehyde 10%) and the identification of normal anatomic structures. Training in the use of ultrasound (transdutor 7.5 MHz). Second period: August/2013- December/2013, case of patients that requiring emergency intubation were analyzed in which airway ultrasound were performed. The anatomo-clinical-surgical / ultrasonographic correlation was analyzed during placement of the endotracheal tube and its identification in the airway. Two hundred twenty ultrasound examinations were performed during tracheal intubation. 134 (60.91%) were made during surgery, 110 (82.09%) were programmed surgery and 24 (17.91%) emergency surgery; and 86 (39.09%) required intubation in shock room. Two groups were classified: Group 1: surgically treated patients (Group A: programed surgery: 104 (94.54%) correctly identified intubation, and in 6 (5.46%) esophageal intubation was detected, and Group B emergency surgery: in 23 (95.83%) correct placement was identified and 1 (4.17%) was esophageal intubation. Group 2: patients intubated in the shock room: 80 (93.03%) were correctly intubated and, 6 (6.97%) had esophageal intubation. In all groups, esophageal intubation was detected only in 13 patients (5.91%), using ultrasound during the procedure. The use of ultrasound for the recognition of the airway, is useful to favor the correct intubation and management of difficult airway. The ultrasound training and anatomo - clinical- surgical application is critical because it would improve the quality of care and decreasing the risk of adverse events.